Robot-assisted Intercostal Nerve Harvesting: A Technical Note about the First Case in Japan - Kiyohito Naito, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2020)
Summary:. Recently, surgical robotic systems have been used to perform microsurgery. Surgical robots have certain properties that make them well suited to microsurgery; for example, they possess 3-dimensional vision, which can be magnified up to 25 times; their movements are up to 5 times more precise than those of surgeons; they possess 7 degrees of wrist articulation; they do not suffer from physiologic tremors; and they can achieve ergonomic surgical positions. The purpose of this study was to report the feasibility of robot-assisted intercostal nerve harvesting in a clinical case. A healthy 57-year-old man suffered a left plexus injury. On diagnosis of clavicular brachial plexus injury, the intercostal nerve transfer to the muscular cutaneous nerve to restore elbow flexion was performed with Da Vinci Xi robot. The harvesting of intercostal nerves using the conventional open approach involves significant surgical exposure, which can lead to perioperative complications. Robot-assisted intercostal nerve harvesting might reduce postoperative pain, shorten patients’ hospital stays, lower complication rates, and produce better quality-of-life outcomes. There are many issues to be solved when performing robotic surgery on peripheral nerves in Japan. However, robot-assisted intercostal nerve harvesting was a feasible surgical procedure, and patient satisfaction was high.